SISTEM KONTROL DAN MONITORING KUALITAS AIR PADA BUDIDAYA IKAN LELE DENGAN MEDIA KOLAM BERBASIS IOT - Nani Anisah; Merinda Tasya Aulia; Eko Sulistyo; Irwan Irwan (Prosiding Seminar Nasional Inovasi Teknologi Terapan, 2022)
Measurement of water turbidity, water pH, and water temperature as well as pond water replacement systems are still done manually, making it difficult for catfish farmers to monitor catfish ponds on a regular basis. Therefore, it is necessary to make a control device for measu ring water turbidity, water pH, and water temperature that can be done automatically and can be monitored via a smartphone. Water quality will be monitored in real time so that the water quality of catfish cultivation is in accordance with catfish culture standards. A good standard of turbidity for catfish 0 -50 NTU, pH 6.5 – 8 and the optimum water temperature for catfish rearing is 25°C - 30°C. The methodology used is the design and manufacture of hardware and software. The hardware used is arduino uno with input turbidity sensor, pH sensor, temperature sensor placed in the pool and ultrasonic sensor in the pool placed at a height of 46cm from the bottom of the pool and ultrasonic sensor placement in the reservoir at a height of 35cm from the bottom of the reservoir. Fish ponds are made using tarpaulins with size D=80cm, T=60cm. To fill the reservoir using a water pump, while the water source uses a 200L drum and drains the pool water using a solenoid valve. The test was carried out by giving the pond a pH of 4.01 -9.18, turbidity 27 -100 NTU, and a temperature of 26 -55⁰C. The test results are recorded in the test table. From the test results, it can be concluded that this tool can measure water turbidity, water pH, and water temperature with a success percentage of 90% and monitoring data on smartphones has a 100% success percentage so that this tool can be used by catfish farmers.